Drug screening approach against mycobacterial fatty acyl-AMP ligase FAAL32 renews the interest of the salicylanilide pharmacophore in the fight against tuberculosis. (1st October 2022) - Le, Nguyen-Hung; Constant, Patricia; Tranier, Samuel; Nahoum, Virginie; Guillet, Valérie; Maveyraud, Laurent; Daffé, Mamadou; Mourey, Lionel; Verhaeghe, Pierre; Marrakchi, Hedia
Graphical abstract: Abstract: Tuberculosis (TB) remains a global health crisis, further exacerbated by the slow pace of new treatment options, and the emergence of extreme and total drug resistance to existing drugs. The challenge to developing new antibacterial compounds with activity against Mycobacterium tuberculosis (Mtb), the causative agent of TB, is in part due to unique features of this pathogen, especially the composition and structure of its complex cell envelope. Therefore, targeting enzymes involved in cell envelope synthesis has been of major interest for anti-TB drug discovery. FAAL32 is a fatty acyl-AMP ligase involved in the biosynthesis of the cell wall mycolic acids, and a potential target for drug discovery. To rapidly advance research in this area, we initiated a drug repurposing campaign and screened a collection of 1280 approved human or veterinary drugs (Prestwick Chemical Library) using a biochemical assay that reads out FAAL32 inhibition. These efforts led to the discovery of salicylanilide closantel, and some of its derivatives as inhibitors with potent in vitro activity against M. tuberculosis. These results suggest that salicylanilide represents a potentially promising pharmacophore for the conception of novel anti-tubercular candidates targeting FAAL32 that would open new targeting opportunities. Moreover, this work illustrates the value of drug repurposing campaigns to discover new leads in challenging drug discovery fields.